Transformational Developments at the Interface of Race, Sport, and the Collegiate Athletic Arms Race in the Age of Globalization - Harry Edwards (University of Kansas Libraries, 2011)
This essay includes a survey and analysis of social, cultural and political factors and forces contouring and configuring the state and trajectory of African-American Sports involvement as we enter the second decade of the 21st Century. These factors include the circumstances and conditions of the traditional Black community; Black educational challenges; the issue of race, justice, and power; and the "collegiate athletic arms race" in the age of globalization in sport and society.